THE IMPACT OF FINANCIAL RATIOS ON THE VALUE OF COMPANIES THAT CONDUCTED M&A WHICH REGISTERED IN IDX ON 2016-2021 - Maria Yvette Duhita; Eko Rizkianto (Dynamic Management Journal, 2023)
This study aims to analyze the impact of the financial ratios such liquidity, solvability, turnover, profitability, and market value, economic value added and operating cash flow on the market value added of corporate mergers and acquisitions that listed in IDX from 2016 to 2021. The research informs influence of independent variables to MVA in companies that do M&A as their business strategy. The sampling technique in this study used non-probability sampling with purposive sampling method. Obtained samples of 19 public companies listed on the IDX and secondary data taken from the Indonesian Stock Exchange website. Financial performance measurement takes place five years before and after M&A. The analytical method uses panel data regression and from panel regression we found that EVA, CR, and ROE are significantly positive influenced with market value added of listed firms in Indonesia that conducted M&A. Our results indicate that earning per share significantly has negative influence to MVA; while DER and TATO are insignificantly negative influenced and OCF is insignificantly positive influenced with market value added.